Kinerja Keuangan, Pengungkapan Corporate Social Responsibility: Dampaknya Pada Nilai Perusahaan: Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020 - Aminah, Aminah; Dinata Pemuka, Riska (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The era of globalization that is increasingly sophisticated and modern today requires that everyone always knows about the information that is developing and up-to-date in society. Like the business world, companies must create and produce good corporate value, so that it looks attractive to stakeholders. Therefore, this study aims to examine the effect of financial performance as proxy for ROA and Corporate Social Responsibility disclosure on firm value as proxy for Tobins'Q. The sample in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2020. In this study using quantitative with secondary data generated from the company's annual financial statements. The sampling technique used is a purposive sampling technique with 25 sample companies within a period of 2 years, from 2019 to 2020. The data analysis used is a combination of panel data between time-series data and cross-sectional data assisted by the Eviews9 program. The results of the study obtained that financial performance proxied as Return On Assets had a positive and significant effect on firm value (Tobins'Q), indicating that the company was able to benefit from the total assets used to operate to earn a profit. Likewise, Corporate Social Responsibility which has a positive and significant effect on firm value (Tobins'Q), means that CSR is able to affect the increase in firm value because the more companies disclose their social disclosure items and the better the disclosure, the higher the impact on firm value, the market will give positive appreciation to companies that carry out Corporate Social Responsibility as indicated by an increase in the company's stock price.